2005
DOI: 10.1016/j.jaut.2005.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the autoantibody repertoire by serological antigen selection

Abstract: The identification of disease related autoantigens targeted by pathogenic T-and B-cell responses is crucial for the development of improved therapies for autoimmune diseases. To identify immunogenic targets recognized by the humoral immune response, we have recently applied a novel and powerful molecular approach, named 'Serological antigen selection'. This method involves the display of a cDNA expression library on filamentous phage and subsequent selection on patient Immunoglobulin G (IgG). In the present st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 32 publications
0
35
0
Order By: Relevance
“…The SAS procedure was performed as described previously (21). In brief, CSF samples of 10 randomly selected untreated relapsing-remitting (RR)-MS patients were pooled and used for affinity selections.…”
Section: Cloning Of a Ms Cdna Library For Pvi Display And Sas Of Phagmentioning
confidence: 99%
See 2 more Smart Citations
“…The SAS procedure was performed as described previously (21). In brief, CSF samples of 10 randomly selected untreated relapsing-remitting (RR)-MS patients were pooled and used for affinity selections.…”
Section: Cloning Of a Ms Cdna Library For Pvi Display And Sas Of Phagmentioning
confidence: 99%
“…Before the start of the selection procedure, CSF samples were absorbed against Escherichia coli and phage components as described in Ref. (21). Following adsorption, pooled CSF was stored at Ϫ80°C.…”
Section: Cloning Of a Ms Cdna Library For Pvi Display And Sas Of Phagmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, Somers et al [97] validated the use of a powerful molecular approach, serological antigen selection [98], for the study of autoantibodies in the CSF or serum of multiple sclerosis patients. The authors used a normalized cDNA library derived from active chronic multiple sclerosis plaques and directionally cloned and displayed the cDNA repertoires on filamentous phage.…”
Section: Profiling Of the Autoantibody Response In Multiple Sclerosismentioning
confidence: 99%
“…However, these investigations employed random peptide libraries to bind IgGs. One limitation of this technique as compared to the newer approach used by Somers et al [97] is that only antigen mimotopes are picked up and further investigations are necessary to identify the actual antigen. Subsequent studies by the same investigators [101,102] indicated that identical antibodies are present both in the serum and CSF albeit a number of them are particularly enriched in the CSF.…”
Section: Profiling Of the Autoantibody Response In Multiple Sclerosismentioning
confidence: 99%